PERAN DAN POLA INTERAKSI PESAN PADA AKUN MEDIA SOSIAL PEMKAB BANGKA - Iksander, Iksander (KOMUNIKASIA: Journal of Islamic Communication and Broadcasting, 2021)
The use of social media as part of e-government development for local governments is an obligation, especially related to the concept of online public relations for every institution in today's digital era. This research was aimed to describe the social media accounts owned by the Bangka Regency Government in supporting the presence of the official site bangka.go.id as well as to define what pattern of message interaction was among the social media accounts. Based on a descriptive analysis using the 7'cs Framework approach, this study found that social media accounts owned by the Bangka Regency Government were classified as non-existent. the second finding is that the message interaction can be classified as one-way patterns where one content on one platform is forwarded to another social media platform without any difference.